2015
DOI: 10.1002/14651858.cd003988.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Combined hormonal versus nonhormonal versus progestin-only contraception in lactation

Abstract: Results were not consistent across the 11 trials. The evidence was limited for any particular hormonal method. The quality of evidence was moderate overall and low for three of four placebo-controlled trials of COCs or POPs. The sensitivity analysis included six trials with moderate quality evidence and sufficient outcome data. Five trials indicated no significant difference between groups in breastfeeding duration (etonogestrel implant insertion times, COC versus POP, and LNG-IUS). For breast milk volume or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 56 publications
0
27
0
3
Order By: Relevance
“…It advises that CHC should not be used before 6 months postpartum by breastfeeding women, unless no other method is available or acceptable (WHO MEC, Category 3) . However, most trials published after 2005 do not report any significant impact of CHC on breastfeeding duration, breast milk composition, or infant growth, and the UK and US guidance recommend that the benefits outweigh the theoretical risks of CHC use after 6 weeks postpartum (Category 2) among breastfeeding women.…”
Section: Methodsmentioning
confidence: 99%
“…It advises that CHC should not be used before 6 months postpartum by breastfeeding women, unless no other method is available or acceptable (WHO MEC, Category 3) . However, most trials published after 2005 do not report any significant impact of CHC on breastfeeding duration, breast milk composition, or infant growth, and the UK and US guidance recommend that the benefits outweigh the theoretical risks of CHC use after 6 weeks postpartum (Category 2) among breastfeeding women.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Cochrane review noted that the quality of evidence regarding hormonal contraception and lactation was moderate overall and low for three of four placebo-controlled trials. 4 The contraceptive implant available in the United States contains ENG, a synthetic progesterone analogue. Serum levels peak at 1,200 pg/mL within the first 2 weeks after insertion and then gradually decline to 202 pg/mL at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence was inadequate to make recommendations regarding hormonal contraceptive use in lactating women. 37 Another systematic review of 43 articles, including 5 randomized trials and 38 observational studies, demonstrated no adverse effects of various progestogen-only methods of contraception on multiple measures of breastfeeding performance when initiated after the immediate postpartum period. Many of these studies also examined infant growth,health,anddevelopmentandfound 932…”
Section: Initiation Of Postpartum Contraceptionmentioning
confidence: 99%